2016
DOI: 10.1089/tmj.2015.0055
|View full text |Cite
|
Sign up to set email alerts
|

VA Telemedicine: An Analysis of Cost and Time Savings

Abstract: Telemedicine at the VA saves travel distance and time, although the reduction in travel payments remains modest at current telemedicine volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
133
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(139 citation statements)
references
References 16 publications
4
133
0
2
Order By: Relevance
“…10 Furthermore, a study published in 2015 showed that in a mental health department of a veterans’ hospital in Vermont, telemedicine use minimized patient travel by 145 miles/visit, with total savings of US$63,000 or 3.5% of the total travel pay disbursement for the year. 11 Another study in rural Kansas showed that a pediatric psychology telemedicine service could save patients an average of US$138 per consult in travel expenses using the conservative metric of US$0.35/mile. 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Furthermore, a study published in 2015 showed that in a mental health department of a veterans’ hospital in Vermont, telemedicine use minimized patient travel by 145 miles/visit, with total savings of US$63,000 or 3.5% of the total travel pay disbursement for the year. 11 Another study in rural Kansas showed that a pediatric psychology telemedicine service could save patients an average of US$138 per consult in travel expenses using the conservative metric of US$0.35/mile. 12 …”
Section: Introductionmentioning
confidence: 99%
“…More commonly, surgical evaluations by telemedicine utilize telephone consultation as a component of the assessment, supplemented with high-resolution imaging and/or videoconferencing. 11 …”
Section: Introductionmentioning
confidence: 99%
“…33 A recent analysis of all telemedicine visits at one Veterans Affairs (VA) hospital over an eight-year period included 5,695 clinical encounters and found that telemedicine resulted in an average travel savings of 145 miles and 142 minutes per visit. 34 These factors, along with reduced time lost from work and fewer inappropriate emergency room visits, result in reduced costs for patients leading to high levels of patient satisfaction. 35 Telemedicine benefits providers as well, as long as it is supported by state legislation and insurer policies.…”
Section: E X Pa Nd I Ng the R E Ach O F Sleep Speci A Li Sts Through mentioning
confidence: 99%
“…For the Veterans Affairs (VA) offices was performed a study, [35], to analyze the travel expenses during the 2005 and 2013-time frame. The study calculated the travel distance and time saved because of tele-medicine, which resulted in an average travel savings of 145 miles and 142 min per visit.…”
Section: Statistics and Impactmentioning
confidence: 99%